From context to interface: Contextual user experience in three student UI/UX projects - Desi Dwi Kristanto (Asosiasi Program Studi Desain Komunikasi Visual Indonesia (Asprodi DKV), 2025)
The design of user interface and user experience (UI/UX) can function not only as a means of aesthetics and navigation, but also as a medium for understanding user behaviour and needs within specific contexts of use. This article offers a reflective multiple‑case analysis of three undergraduate digital application design projects that adopt context‑based approaches to address functional, social and emotional issues faced by their users. Drawing on human‑centered design standards and contextual user experience concepts, the study examines how each project configures users, tasks and environments, and how experience‑centered design perspectives are mobilised to shape affective qualities such as safety, reassurance, productivity and community engagement. Using documentation of the design process, design artefacts and final reports, the analysis shows how observation, interviews, persona and journey mapping, and prototype testing enabled students to surface patterns of interaction, latent needs and contextual constraints that informed their interface decisions. The findings argue that a deep understanding of context of use and lived experience is crucial for generating UI/UX solutions that are not only usable and visually coherent, but also empathetic, inclusive and aligned with users’ everyday practices. In the realm of design education, the study suggests that treating UI/UX projects as sites for contextual and experience‑centered inquiry can strengthen students’ reflective capacities and position interface design as a research‑driven strategy for mediating relationships between humans and technology.